Dynamic simulation of a gas turbine for heat recovery at varying load and environment conditions. (August 2021) - Gou, Xiang; Zhang, Han; Li, Guangyao; Cao, Yuhao; Zhang, Qiyan
Highlights: A three-stage waste heat recovery model integrating engineering needs is presented. The model is simulated dynamically using Aspen Hysys. High gas turbine load varying rate weakens the stability of the system. System stable state is independent of disturbance rate, but relies on the amplitude. Abstract: A novel solution of three-stage waste heat recovery from a gas turbine (11.35 MW) is proposed and its dynamic response characteristics with a series of load and environment change in the process of gas turbine operation is studied according to actual process requirements on an offshore platform. Integrating three processes under different temperature ranges is performed by using the flue gas to heat oil, generate steam and heat rejection water in turn with three heat exchangers (HE I, HE II and HE III), respectively. The dynamic simulation results show that the steam flow rate in HE II has obvious fluctuations as gas turbine load drops. Within the 10%, 20%, and 30% load decrease of gas turbine, the stabilized values of steam mass flow rate decrease by 7.6%, 16.3%, and 26.5%, respectively. The greater varying rate of the gas turbine load can accelerate the response speed but deteriorates system stability. The environment temperature change from 5 °C to 25 °C essentially affects the flue gas temperature from 473.18 °C to 496.70 °C, and it influences the system response linearly to a certain extent for the non-linear system expect for HE II. Since the phase transition process exists in HE II and the gas residence time is much shorter than liquid, the response speed and trend is different from the process in HE I and HE III.